Monetary policy transmission and house prices, a VAR approach: a case study of South Africa (1994 to 2011) - Mutsvunguma, Priscilla Tatenda (My University, 2013)
We analyse the role of financial and macro-economic variables in the conduct of monetary policy, particularly the role played by monetary policy in the house price boom of the early 2000s. The analysis is performed in the setup of a New Keynesian open economy. We estimate a five variable Recursive Vector Autoregressive model consisting of the short term interest rate, house prices, inflation, output and the exchange rate. Quarterly data from 1994 to 2011 was inputted in Eviews (6) to run the model. We find a significant causal relationship between the short term interest rate and house prices; the impulse response results show an instant response of house prices to a shock in monetary policy. We conclude that the house price boom of the early 2000s was partially attributed to an overreaction to a shock in monetary policy. We also find evidence of exchange rate pass- through to the consumer price index as in (Mishkin, 2008).We conclude that perhaps monetary policy should take cognisance of asset price fluctuations and exchange rate volatility in determining the policy instrument
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Monetary policy; House prices; South Africa; Inflation; Exchange rate volatility